On a Specific Intermolecular Interactions in Nematic Liquid Crystal Systems - Bezhanova, L. S.; Atanesyan, A. K.; Sukiasyan, R. P.
The aim of this study was the investigation of the molecular structure of Nematic Liquid Crystal Systems that are based on polar liquid crystals, whose molecules have a large dipole moment directed along the long axis of the molecule. The investigation has a practical importance in the development of the new LC materials for electro-optical systems. In this work, the investigation of a specific intermolecular interaction – the formation of charge transfer complexing (CTC) in LC systems − was carried out by UV and IR spectroscopy. A long−wavelength shift of the CTC absorption band is found. The complicated dependence of optical density of the absorption band of the donor and CTC on the initial donor concentration has been obtained. The correlation between the optical density of the absorption bands of the CTC and donor, on the one hand, and the phase diagram, on the other, was demonstrated to occur in the investigated systems. The analytical expressions for equilibrium constants of complexation process were derived, and the concentrations of the complexes were determined based on the absolute rates reaction theory.
Keywords: Physics